2016
DOI: 10.1097/md.0000000000004790
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of deep-seated facial microcystic lymphatic malformations with intralesional injection of pingyangmycin

Abstract: Treatment of microcystic lymphatic malformations (LMs) is still a great challenge to physicians in the field of managing vascular anomalies. Several kinds of treatment have been proposed for microcystic LMs, but the responses to these treatment modalities vary considerably among individuals. The aim of the study was to investigate the safety and efficacy of intralesional injection of pingyangmycin for microcystic LMs located in the deep facial region.Twenty-one consecutive patients with deep-seated facial micr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 31 publications
(41 reference statements)
0
7
0
Order By: Relevance
“…Comparison with the weight and tumor volume of mice, it was found that weight is stable for control group, a smaller light weight in PYM+DNP treatment group while tumor volume keeps smaller than the control group, that is good signs for control tumor growth. PYM is a clinically anticancer drug which is used for certain cancer patients [17][18][19][20] , also used for local injection in the past. Today, it is first time for intratumoral injection of PYM with DNP, it may not change the function of PYM, but it may let the PYM to play an important role with DNP separately.…”
Section: Discussionmentioning
confidence: 99%
“…Comparison with the weight and tumor volume of mice, it was found that weight is stable for control group, a smaller light weight in PYM+DNP treatment group while tumor volume keeps smaller than the control group, that is good signs for control tumor growth. PYM is a clinically anticancer drug which is used for certain cancer patients [17][18][19][20] , also used for local injection in the past. Today, it is first time for intratumoral injection of PYM with DNP, it may not change the function of PYM, but it may let the PYM to play an important role with DNP separately.…”
Section: Discussionmentioning
confidence: 99%
“…13 However, sclerotherapy may contribute to the buildup of scar tissue and may allow LM recurrence and regrowth. 11 Sclerotherapy, particularly using bleomycin 12 or pingyangmycin, 14 has been utilized to treat microcystic lymphatic disease, which rarely is surgically excisable given the infiltrative pattern of LM. In our experience, results from individual procedures are modest, whereas sequential sclerotherapy procedures can provide benefit but require serial anesthesia and acceptance of sclerosant risks.…”
Section: Introductionmentioning
confidence: 99%
“…It is considered that microcystic lymphangiomas tend to be more resistant to treatment than macrocystic lymphangiomas possibly because there are no obvious cysts to target within the lesion. 46 The therapeutic effect on large diffuse lesions was poor. 46…”
Section: Summary Of Main Resultsmentioning
confidence: 99%